Entry Cost, financial friction, and cross-country differences in income and TFP - Lei Fang (Federal Reserve Bank of Atlanta, 2010)
This paper develops a model to assess the quantitative effect of entry cost and financial friction on cross-country income and total factor productivity (TFP) differences. The main focus is on the interaction between entry cost and financial friction. The model is calibrated to match establishment-level statistics for the U.S. economy assuming a perfect financial market. The quantitative analysis shows that entry costs and financial frictions together can generate a factor ten of the differences in income per capita and a factor five of the differences in TFP, and a large part of the differences are accounted for by the interaction between entry cost and financial friction. The main mechanism is that financial friction amplifies the effect of entry cost by boosting the effective entry cost.
Keywords: O11; O43; 330; entry cost; financial friction; GDP per capita; TFP